2017
DOI: 10.1021/acscatal.6b02966
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic-Framework-Derived Fe-N/C Electrocatalyst with Five-Coordinated Fe-Nx Sites for Advanced Oxygen Reduction in Acid Media

Abstract: Even though Fe-N/C electrocatalysts with abundant Fe-N x active sites have been developed as one of the most promising alternatives to precious metal materials for oxygen reduction reaction (ORR), further improvement of their performance requires precise control over Fe-N x sites at the molecular level and deep understanding of the catalytic mechanism associated with each particular structure. Herein, we report a host−guest chemistry strategy to construct Fe-mIm nanocluster (NC) (guest)@zeolite imidazole frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
283
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 501 publications
(299 citation statements)
references
References 34 publications
11
283
0
Order By: Relevance
“…Previously studies proposed that the Fe-N x moieties or the N doped carbon activated by Fe species account for the brilliant ORR performance. 7,16,36 Here further experiments were conducted to research these factor. We investigated the ORR catalytic activity of HP-Fe-N/CNFs-HT1 before and after acid leach (HP-Fe-N/CNFs-AL), as shown in Figure S7.…”
Section: Resultsmentioning
confidence: 99%
“…Previously studies proposed that the Fe-N x moieties or the N doped carbon activated by Fe species account for the brilliant ORR performance. 7,16,36 Here further experiments were conducted to research these factor. We investigated the ORR catalytic activity of HP-Fe-N/CNFs-HT1 before and after acid leach (HP-Fe-N/CNFs-AL), as shown in Figure S7.…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, one of the most promising candidates to replace PMs as ORR catalyst is single‐atom Fe embedded nitrogen‐doped carbon (Fe–N–C), where FeNx moieties formed by coordination of single‐atom Fe with nitrogen embedded in carbon matrix are regarded as active sites for ORR . However, due to the thermodynamical instability, single‐atom Fe is prone to migration and agglomeration into nanoparticles during pyrolysis, resulting in lower utilization of metal species, decrement of FeN x active site, and thereby poor catalyst performance . Numerous efforts have been made into controllable synthesis of Fe–N–C catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Zeolite imidazolate frameworks (ZIFs) is a class of materials composed of metal ion and dimethyl imidazole linker, and in view of the special 3D network structure and flexible adjustability, they have widely used in many fields including gas storage/separation, drug delivery, electrode materials, and catalysis . Recently, zinc‐based ZIF‐8 shows great potential as carbon precursor in the fabrication of Fe–N–C, because Zn vaporizes at above 900 °C, leaving N‐doped carbon skeletons with homogenous pore, beneficial for the diffusion of the reactants during catalysis . Although numerous Fe‐containing compounds were investigated in previous reports to synthesize ZIF‐derived Fe–N–C materials, agglomerated Fe/Fe 3 C particles were usually observed after pyrolysis …”
Section: Introductionmentioning
confidence: 99%
“…Such structures have been shown to form carbonaceous matrices doped with residual inorganic components upon pyrolysis. This strategy has been successfully applied to make FeN x single‐site electrocatalysts, using N‐containing linkers such as 2‐aminoterephthalic acid, dicyanoimidazole and 2‐methylimidazole . For a more general overview of MOF as precursors to electrocatalysts, readers are invited to consult more general reviews …”
Section: Fenx For Electrocatalysismentioning
confidence: 99%
“…The subsequent host‐guest interactions resulted in different types of FeN x sites (x=2 to 5) on the porous carbon matrix. Their combined experimental‐theoretical scrutiny revealed that penta‐coordinated FeN 5 sites significantly promoted the ORR reaction rate in acid media, due to the small energy barrier and the low adsorption energy of intermediate OH on these sites …”
Section: Fenx For Electrocatalysismentioning
confidence: 99%